Analysis of Brand Awareness and Brand Image on Brand Equity Over Customer Implications to Purchase Intention at PT. SGMW Motor Indonesia (Wuling, Indonesia) - Irpan Irpan; Endang Ruswanti (Journal of Multidisciplinary Academic, 2020)
Nowadays, a high competition in the business environment is the main issue, causing companies have difficulty to increasing the number of customers. This also happens in Automotive industries, which is so many big competitor. Here, a strong brand awareness and brand image is needed for new brand of product so that can be affect the value of brand equity, that it will have an impact on the intention to buy from potential customers and increase sales. In this study, we analyze whether Brand Awareness and Image can significantly mediate the value of Brand Equity that can increase Consumers Purchase Intention from a Consumers of PT SGMW Motor Indonesia (Wuling Indonesia). Here, we use a quantitative method with a Likert scale to measure Brand Awareness influences Brand Equity, Brand Image influences Brand Equity, and Brand Equity influences Consumer Buying Intention also the research design to find relationship between two or more variables using LISREL. The benefits of research for academics are expected to be as a reference material. The Benefits of research for companies to evaluate sales and marketing strategies so they can take initiatives in increasing sales and revenue.